Variations and drivers of evapotranspiration in the Tibetan Plateau during 1982–2015 - Chang, Yaping; Ding, Yongjian; Zhang, Shiqiang; Qin, Jia; Zhao, Qiudong (Journal of hydrology. Regional studies, 2023)
The Tibetan Plateau Evapotranspiration (ET) plays a critical role in the water balance, energy budget, and carbon cycle. However, the variations, trends, and controls of ET on the Tibetan Plateau (TP) are poorly understood because of uncertainties in ET estimates and sparse observations. In this study, the variations in ET and its components and their drivers and controls in the TP were analyzed at seasonal and annual scales during 1982–2015. Spatially, the multiyear mean annual ET decreased from the southeastern to northwestern TP. Canopy transpiration (Ec) was the main component of ET (52.7%), followed by soil evaporation (Es) (34.4%) and interception (Ei) (10.7%). Regionally, the averaged ET and its components increased significantly at the seasonal and annual scales. Spatially, the controlling factor for ET changed from water to energy as the climatic zones transferred from aridity to humidity. The annual ET was controlled by soil moisture (SM) in arid and semi-arid zones, whereas Ta was the dominant factor in the other regions. The increased annual Es and Ei were primarily caused by SM, while the annual Ec was determined by Ta. In addition, NDVI played a certain role in regulating the annual Ec and Ei variations. This study improves our understanding of hydrological processes and water resource management under global climate change. [Display omitted] •Annual ET and its components increased significantly during 1982–2015 in the TP.•Soil moisture was the dominant variable affecting variation in ET, followed by temperature.•Different ET components displayed contrasting responses to environmental drivers.•Impact of vegetation greening on canopy transpiration and interception cannot be neglected.